Toxicity evaluation induced by single and 28-days repeated exposure of withametelin and daturaolone in Sprague Dawley rats - Baig, Muhammad Waleed; Majid, Muhammad; Nasir, Bakht; Hassan, Syed Shams ul; Bungau, Simona; Haq, Ihsan-ul (Frontiers in Pharmacology, 2022)
Safe preclinical dose determination is predictive of human toxicity and can have a profound impact on the overall progress of the compound in early drug discovery process. In this respect, current study sought to investigate for the first time the acute and subacute oral toxicity of two pharmacologically active natural compounds i.e., withametelin and daturaolone in Sprague Dawley rats. As per acute toxicity studies, withametelin and daturaolone were characterized as GHS category 4 and 5 compounds, respectively. Sub-acute daily dose of withametelin was 5, 2.5 and 1.25 mg/kg but, for daturaolone, it was 10, 5 and 2.5 mg/kg. High dose (5 and 2.5 mg/kg) withametelin groups showed dose dependent changes in the general, hematological, biochemical and histopathological parameters in both sexes, the most prominent being hyperthyroidism while no toxicity was observed at lower doses (1.25 and 0.75 mg/kg), NOAEL being 1.25 mg/kg. Daturaolone was comparatively safer and showed dose dependent significant changes in hepatic enzymes, bilirubin, creatinine, and glucose levels while histological changes in testes were also observed. Lower doses (5, 2.5 and 1.25 mg/kg) of daturaolone showed no significant toxic effects and 5 mg/kg was declared as its NOAEL. Long term and interspecies toxicological studies are required for further validation. Depending upon our findings, starting effective oral dose levels of 1.25 mg/kg/day for withametelin and 5 mg/kg/day for daturaolone are proposed for repeated dose (up to 28 days) preclinical pharmacological evaluation models.